The Relationship between Movement Control Order Impact Factors and Construction Project Performance - Er , Hui Xing; Ismail, Radzi; Hasmori, Muhammad Fikri; Dan, Wang (International Journal of Sustainable Construction Engineering and Technology, 2023)
The Malaysian government’s pursuit of the Movement Control Order (MCO) had a severe impact on the performance of the construction project, which was hampered as a result of their actions. It becomes even more difficult when the region around construction projects is defined as a “red zone”. This situation affects the performance of construction projects, which is related to project delays, increase in construction costs, waste of construction materials, labourers who have not received any salary, lack of labour, and etc.  This paper attempts to investigate the relationship between MCO impact factors and the performance of construction projects in Malaysia. The quantitative technique was applied in this study. The contractors registered under the Construction Development Board (CIDB) in the state of Selangor were chosen as the respondents. In total, 100 respondents participated and gave full support for this study. This relationship was investigated using a correlation analysis technique. The highest impact is the construction cost. The construction costs increased due to the increase in the prices of construction materials and machinery, lack of labours, and additional expenses for COVID-19 precautions. The findings found that the larger the negative impact of MCO’s actions during the COVID-19 outbreak on time, cost, and resources, the worse the performance of Malaysian projects will be in general. These factors should be considered by the government before a decision is made. For future research, it is suggested to look at how the regulation can assist the construction stakeholders to ensure the MCO does not have a big impact on the construction projects.